Pengembangan Perangkat Pembelajaran Matematika Menggunakan Model Discovery Learning pada Materi Bangun Ruang Sisi Lengkung Kelas IX SMP/ MTs - Patricia, Putri; Anggraini, Rini Dian; Maimunah (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
This study aims to create mathematics learning devices such as a syllabus, lesson plans, and student worksheets for the 9th grade of junior high school using discovery learning on curved face three-dimensional (cylinder, cone, and sphere) material. The incompatibility instruments arranged by the teacher based on the 2013 Curriculum inspired this research. The 4-D development model was used in this study, and it consists of defining, designing, developing, and disseminating stages. The validation sheet and student response questionnaires were the instruments used in this study. The learning that was developed was validated by three of the validators and revised based on their suggestions. With very valid categories, the average score of the validation results for the syllabus is 3,79, lesson plans are 3,81, and student worksheet is 3,73. This validation indicates that the syllabus, lesson plans, and student worksheet can be sampled. Then, in small groups, valid student worksheets are tested. The average percentage of small group trial results for student worksheets is 92,29 percent, with a very practical category. Based on the results of data analysis and discussion, it can be concluded that syllabus, lesson plans, and student worksheets by using discovery learning on curved face three dimensional material for the 9th grade of junior high school has fulfilled valid